Model of Strengthening Health Literacy and Prevention of Hypertension Based on Family Independence - fitriah fitriah; Suryaningsih -; Rodiyatun - (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Abstract Hypertension is often referred to as the silent killer because it is a deadly disease accompanied by early symptoms for people with hypertension. The prevalence of hypertension continues to increase sharply and it is predicted by 2025 as many as 29% of adults, but the tendency to do prevention independently is still low. Prevention of hypertension can’t be separated from the risk factors that exist in the family, including an unhealthy lifestyle. Family involvement in early detection needs to develop and modified so that every family member can reduce risk factors. The brief background of the topic and significance of the study. This study aims to collect information on the family of ability in health literacy as a solution to increase family independence in preventing hypertension. This study is used for research and development (R&D), which is the first of 3 research stages planned to be completed in 3 years. The research design was cross-sectional. The study was conducted on families in Bangkalan Regency with a sample of 150 people from 4 sub-districts representing mountainous, urban, rural, and coastal areas, namely Bangkalan, Kedundung, Sukolilo, and Kokop sub-districts taken by random cluster sampling. Data was collected using questionnaires and analyzed using Partial Least Square Path Modeling. This study has obtained ethically appropriate information through the Research Ethics Committee of the Health Polytechnic of the Ministry of Health Surabaya with the number EA/940/KEPK-Poltekkes Sby/V/2022. The results show that the demographic characteristics of the family have an effect on health literacy in preventing hypertension. Families with good health literacy can increase independence in preventing hypertension. Families who achieve a high level of independence will be able to prevent hypertension. The use of digital literacy can be a solution to improve people's health literacy skills. Materials from health literacy are made simpler but right on target. Supported by more complex forms of communication such as interactive video. Application usage to advance the knowledge of patients' hypertension can increase the independence of hypertension.